A Study of the Essential Oils of Four Sudanese Accessions of Basil (Ocimum basilicum L.) Against Anopheles Mosquito Larvae - M. M., Yusoff; Azhari, H. Nour; Elhussein, Salah A.; Osman, Nour A.; Nour, A. H. (Science Publications, 2009)
Problem statement: Certain basil essential oils were claimed to have a larvicidal activity towards mosquito’s larvae. To test this claim the essential oils of four accessions of basil grown in Sudan were selected and tested for Anopheles larvae. Malaria is the major health problem in the Sudan and the whole country is now considered endemic, with varying degrees, about 35,000 deaths every year due to malaria. Anopheles mosquito is the major vector of malaria disease in Sudan. Search for larvicidal active compound(s) is one of several attempts to fine effective and affordable ways to control this mosquito. To determine the toxic effects of basil essential oils extracted by steam distillation against Anopheles larvae. Approach: For the larvicidal bioassay, three concentrations (100,300, 500 ppm) of essential oil solutions of four basil accessions were prepared; 1 mL of ethanol was used to solubilize the oil in water (999 mL). In each concentration of oil solution were inserted 20 larvae (third instars). A set of controls using 0.1% ethanol and untreated sets of larvae in (tap) water, were also run for comparison. Data were evaluated through regression analysis, from the regression line; the LC50 values were read. The active ingredients were separated and/ or identified by TLC, IR and GC-MS. Results: Larvicidal activity of the essential oils is varied, lasted for about 9 h and thereafter decreased, LC50 values ranging from 190-300 ppm. Linalool, geraniol and eugenol are active components of basil essential oil against Anopheles larvae. Two accessions were caused 100% mortality at a concentration range 300-500 ppm for 3 h. Conclusion: These results indicated that basil essential oils have larvicidal activity towards Anopheles larvae. Therefore, could be affordable way to control this mosquito.